A FtsZ cis disassembly element acts in Z-ring assembly during bacterial cell division - Huijia Yin; Yang Liu; Ying Zhao; Pengyue Chen; Zengyi Chang (Nature Communications)
Abstract Bacterial cell division hinges on the Z-ring, an architecture built from the dynamical assembly and disassembly of FtsZ proteins. This delicate balance ensures not only apparent stability, but also continuous remodeling, both of which are required for Z-ring functioning. However, the molecular nature of such subcellular structures remains elusive. Here, by identifying all amino acid residues participating in FtsZ self-assembly in Escherichia coli, we show that the extreme N-terminal intrinsically disordered region (N-IDR) of FtsZ acts as a cis disassembly element that contacts and disrupts the longitudinal interface, tipping the balance more toward polymer disassembly. This previously unappreciated structural characteristic is indispensable for promoting Z-ring architecture condensation at midcell (rather than elsewhere) upon modulation by certain trans-acting factors (such as the E. coli MinC protein).